A história de Arroio dos Ratos/RS no contexto da mineração: fundamental I - Gonçalves, Valdeci dos Santos (2024)
The present work “The History of Arroio dos Ratos in the Context of Mining: Fundamental I”, arises from the need to produce material that could assist teachers in the classroom, seeking to provide historical content on Local History and Historical Heritage, primarily for fundamental I, about mining in Arroio dos Ratos/RS.This demand results from the perception, as a pedagogue and graduate in history, of subjects suitable for this stage of basic education, in the local context. The objective of the investigation was to contribute to the teaching of local history in the early years of elementary school, developing didactic material to support the teaching of the History of mining in Arroio dos Ratos/RS. In this sense, we seek to answer the following question: How is it possible to work on the importance of Local History regarding the issue of mining, in the early years in the municipality of Arroio dos Ratos?To this end, we carried out bibliographical, documentary and field research. Our applied research consisted of developing a product, in accordance with CAPES Ordinance No. 171/2018, which was a pedagogical resource in the form of a didactic notebook, composed of texts and activities, presenting the theme of the local history of Arroio dos Ratos/ RS taking the issue of mining as a reference to be used preferably in elementary school I. Some of the activities present in the Notebook were used during the second half of 2023.